EVIDENCE FOR INTERGENIC COMPLEMENTATION IN HYBRID CELLS DERIVED FROM TWO HUMAN DIPLOID STRAINS EACH CARRYING AN X-LINKED MUTATION - Siniscalco, Marcello (1969)
Two male diploid fibroblast strains, each carrying deficiency mutations at different X-linked loci (glucose-6-phosphate dehydrogenase and hypoxanthine-guanine-phosphoribosyltransferase) have been successfully hybridized. The resulting mononucleated hybrid cells have been shown to synthesize both normal gene products, indicating that both X chromosomes are functionally active in the hybrid cells. We believe this is the first reported example of intergenic complementation in fused human diploid cells.